Determination of the prevalence of Toxoplasmosis among cat breeders at home and its relationship to abortion. - البرهوم, وعد; حسن محمد سلمان ,; يوسف أمين زريق , (Latakia University Journal -Biological Sciences Series, 2023)
This study included 100 samples of women attending Tishreen university Hospital in Lattakia, with the aim of determining the prevalence of Toxoplasmosis among cat breeders and its relationship to abortion, by determining the titer of IgG &IgM antibodies using the direct immune fluorescence test, during the period from December 2021 to June 2022. The total parasite prevalence rate in this study samples was 51% and the test results showed that the prevalence rate of Toxoplasmosis among women who kept cats at home (32 out of 39) was 82,05%, while the rate of prevalence among women who did not keep cats at home (19 out of 61) reached 31,14% and there was a strong correlation between breeding cats and infection with the parasite P<0,05. As for pregnant women (4 out of 6), the prevalence rate was 66% for them, and there was no correlation between pregnancy and infection with the parasite. The prevalence rate for pregnant women who kept cats at home (3out of 6) was 50%, and there was no correlation between keeping cats and infection with the parasite among pregnant women p>0.05.